PENGGGUNAAN ZOOM MEETING DALAM PEMBELAJARAN JARAK JAUH PADA MASA PANDEMI COVID-19 DI SMPN 164 JAKARTA - Zulfitria Zulfitria; Annisa Handayani; Zainal Arif (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
This research is motivated by the results of case studies in the world of education during the Covid-19 pandemic, the education system is faced with a situation that requires teachers to be able to master distance learning media. During the Covid-19 pandemic, every school implemented a distance learning system. An application that is widely used during distance learning is Zoom Meeting. The purpose of this research is to find out 1) student responses in easy access to the Zoom Meeting application, 2) understanding of the material in learning using the Zoom Meeting application, 3) the effectiveness of using the Zoom Meeting application in online learning, 4) Use of Zoom Meeting in mathematics learning. This research method uses descriptive research methods using survey techniques. The research instruments used were questionnaires and online interviews which were given to 38 students of SMPN 164 Jakarta consisting of 3 generations in the even semester. The results showed that 52.93% of students expressed disagreement in the ease of accessing the Zoom Meeting application, 62.63% of students agreed in understanding the learning material using the Zoom Meeting application, 60.42% of students agreed on the effectiveness of using the Zoom Meeting application , and 46.74% of students agreed to use the Zoom Meeting application in learning mathematics. The results of this study indicate that the use of the Zoom Meeting application is not very effective for students of SMPN 164 Jakarta. However, the Zoom Meeting application is better because in the Zoom Meeting application communication between individuals is carried out orally compared to the use of learning applications that carry out communication activities in writing according to educational communication theory.